Small streams–large concentrations? Pesticide monitoring in small agricultural streams in Germany during dry weather and rainfall. (15th September 2021) - Halbach, Katharina; Möder, Monika; Schrader, Steffi; Liebmann, Liana; Schäfer, Ralf B.; Schneeweiss, Anke; Schreiner, Verena C.; Vormeier, Philipp; Weisner, Oliver; Liess, Matthias; Reemtsma, Thorsten
Highlights: Comprehensive pesticide monitoring at 105 sites over two application periods. RAC exceedances occurred for majority of small streams. Rainfall increases pesticide concentrations in streams by factor of 10. 2, 4-D, MCPA, terbuthylazine, and nicosulfuron increased most strongly during rainfall. Sum concentration of pesticide metabolites factor 10 higher than pesticides. Abstract: Few studies have examined the exposure of small streams (< 30 km 2 catchment size) to agriculturally used pesticides, compared to large rivers. A total of 105 sites in 103 small agricultural streams were investigated for 76 pesticides (insecticides, herbicides, fungicides) and 32 pesticide metabolites in spring and summer over two years (2018 and 2019) during dry weather and rainfall using event-driven sampling. The median total concentration of the 76 pesticides was 0.18 µg/L, with 9 pesticides per sample on average (n = 815). This is significantly higher than monitoring data for larger streams, reflecting the close proximity to agricultural fields and the limited dilution by non-agricultural waters. The frequency of detection of all pesticides correlated with sales quantity and half-lives in water. Terbuthylazine, MCPA, boscalid, and tebuconazole showed the highest median concentrations. The median of the total concentration of the 32 metabolites exceeded the pesticide concentration by more than an order of magnitude. During dry weather, the median total concentration of the 76 pesticides was 0.07 µg/L, with 5 pesticides per sample on average. Rainfall events increased the median total pesticide concentration by a factor of 10 (to 0.7 µg/L), and the average number of pesticides per sample to 14 (with up to 41 in single samples). The concentration increase was particularly strong for 2, 4-D, MCPA, terbuthylazine, and nicosulfuron (75 percentile). Metabolite concentrations were generally less responsive to rainfall, except for those of terbuthylazine, flufenacet, metamitron, and prothioconazole. The frequent and widespread exceedance of the regulatory acceptable concentrations (RAC) of the 76 pesticides during both, dry weather and rainfall, suggests that current plant protection product authorization and risk mitigation methods are not sufficient to protect small streams. Graphical abstract: Image, graphical abstract